A probabilistic atlas of the human thalamic nuclei combining ex vivo MRI and histology - Iglesias, Juan Eugenio; Insausti, Ricardo; Lerma-Usabiaga, Garikoitz; Bocchetta, Martina; Van Leemput, Koen; Greve, Douglas N.; van der Kouwe, Andre; Fischl, Bruce; Caballero-Gaudes, César; Paz-Alonso, Pedro M. (NeuroImage (Orlando, Fla.), 2018)
The human thalamus is a brain structure that comprises numerous, highly specific nuclei. Since these nuclei are known to have different functions and to be connected to different areas of the cerebral cortex, it is of great interest for the neuroimaging community to study their volume, shape and connectivity in vivo with MRI. In this study, we present a probabilistic atlas of the thalamic nuclei built using ex vivo brain MRI scans and histological data, as well as the application of the atlas to in vivo MRI segmentation. The atlas was built using manual delineation of 26 thalamic nuclei on the serial histology of 12 whole thalami from six autopsy samples, combined with manual segmentations of the whole thalamus and surrounding structures (caudate, putamen, hippocampus, etc.) made on in vivo brain MR data from 39 subjects. The 3D structure of the histological data and corresponding manual segmentations was recovered using the ex vivo MRI as reference frame, and stacks of blockface photographs acquired during the sectioning as intermediate target. The atlas, which was encoded as an adaptive tetrahedral mesh, shows a good agreement with previous histological studies of the thalamus in terms of volumes of representative nuclei. When applied to segmentation of in vivo scans using Bayesian inference, the atlas shows excellent test-retest reliability, robustness to changes in input MRI contrast, and ability to detect differential thalamic effects in subjects with Alzheimer's disease. The probabilistic atlas and companion segmentation tool are publicly available as part of the neuroimaging package FreeSurfer. [Display omitted] •A probabilistic atlas of the human thalamus (26 nuclei) derived from histology.•3D histology reconstruction assisted by ex vivo MRI and blockface photographs.•Companion Bayesian method segments the nuclei from in vivo scans of any MRI contrast.•Method has excellent test-retest reliability and detects differential effects in AD.•The method is publicly available as part of FreeSurfer.